Analisa Dampak Variasi Parameter Temperatur Injeksi dan Waktu Pendinginan Terhadap Cacat Produk Cap Tube Oval Pada Proses Injection Moulding - Agus Kholistiyanto; Sulistyono Sulistyono (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Plastic products are materials that we commonly encounter in everyday life, the use of goods made from plastic raw materials is increasing. Starting from products with simple shapes such as food and beverage packaging, household appliances, kitchen utensils, cosmetic containers, to automotive component products. The plastic injection molding process requires a variety of precise setting parameters, some of which concern heating temperature, amount of material used, cooling system, mold holding time, injection speed, and other parameters. These parameters are things that affect product quality and defects. Another reason for product defects is that the process parameter settings have not been standardized and the trial and error method is still used, so the results are not optimal. One of the defects that occurs in the oval tube cap product is a loose top cap defect (cannot close). This study aims to determine the effect of injection temperature and cooling time on loose top cap defects in oval tube cap products. This study uses quantitative research by conducting repeated experiments to collect data, this method is carried out by varying the injection temperature parameters, namely 210 ° C, 220 ° C, and 230 ° C with a cooling time of 8 seconds, 10 seconds, and 12 seconds. The results obtained from this study are that if the injection temperature used is lower, the level of defects that occur will be higher, while if the selection of a higher cooling time, the level of defects that occur will be lower. From this research, the correct parameters can be obtained at an injection temperature of 220 °C and a cooling time of 12 seconds.